YouTube-videos for patient education in lymphangioleiomyomatosis? - Wilkens, Finn M.; Ganter, Claudia; Kriegsmann, Katharina; Wilkens, Heinrike; Kahn, Nicolas; Goobie, Gillian C.; Ryerson, Christopher J.; Kreuter, Michael (Respiratory research, 2022)
The Internet is commonly used by patients to acquire health information. To date, no studies have evaluated the quality of information available on YouTube regarding lymphangioleiomyomatosis (LAM). Our aim was to determine the quality and content of YouTube videos regarding LAM and to compare the information provided with current knowledge and guidelines about the disease.
Gesehen am 30.05.2022